Login

Register Now

Lorem ipsum dolor sit amet, consectetur adipiscing elit. Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu. Fusce viverra neque at purus laoreet consequa. Vivamus vulputate posuere nisl quis consequat.

Register Now

Lost Password

Lost your password? Please enter your username and email address. You will receive a link to create a new password via email.

5x - 3y = 8; 3x + y = 2

5x - 3y = 8; 3x + y = 2

Print or Save

5x - 3y = 8. . . (I)
3x + y = 2 . . . (II)

Multiplying both sides of equation (II) by 3.

9x + 3y = 6 . . . (III)
5x - 3y = 8. . . (I)

Now let us add equations (I) and (III)

  5x - 3y = 8
+ 9x + 3y = 6
 
14x = 14
x = 1

substituting x = 1 in equation (II)

3x + y = 2
∴ 3×1 + y = 2
∴ 3 + y = 2
∴ y = -1

solution is x = 1, y = -1;

it is also written as (x, y) = (1, -1)

SÉå cÉUÉÇMüÉåÇ uÉÉsÉå UåZÉÏrÉ xÉqÉÏMüUhÉ May 24 , 2018 0 Comments 60 views